PRR-signaling pathways: Learning from microbial tactics. Issue 2 (March 2015) - Sellge, Gernot; Kufer, Thomas A.
Highlights Pathogens use multiple PRR subversion mechanisms to establish infections. The host can sense bacterial-induced modifications of signaling events. Activation and alterations of PRR-signaling by commensals assures homeostasis.